An Experimentally Determined State Diagram for Human CD4(+) T Lymphocyte CXCR4-Stimulated Adhesion Under Shear Flow - Anderson, Nicholas R. (Cell Mol Bioeng, 2018)
INTRODUCTION: The leukocyte adhesion cascade is important for the maintenance of homeostasis and the ability of immune cells to access sites of infection and inflammation. Despite much work identifying the molecular components of the cascade, and numerous simulations to predict the relationship between molecule density, identity, and adhesion, these relationships have not been measured experimentally. METHODS: Using surfaces functionalized with recombinant ICAM-1 and/or E-selectin along with immobilized SDF-1α, we used a flow chamber to measure rates of tethering, rolling and arrest of primary naïve human CD4(+) T lymphocytes on different surface densities of ligand. RESULTS: Cells required a minimum level of ligand density to progress beyond tethering. E-selectin and ICAM-1 were found to have a synergistic relationship in promoting cell arrest. Surfaces with both ligands had the highest levels of arrest, while surfaces containing only E-selectin hindered the cell’s ability to progress beyond rolling. In contrast, surfaces of ICAM-1 allowed only tethering or arrest. Cells maintained constant rolling velocity and time to stop over large variations in surface density and composition. In addition, surface densities of only O(10(1)) sites/µm(2) allowed for rolling while surface densities of O(10(2)) sites/µm(2) promoted arrest, approximately equal to previously determined simulated values. CONCLUSIONS: We have systematically and experimentally mapped out the state diagram of T cell adhesion under flow, directly demonstrating the quantitative requirements for each dynamic state of adhesion, and showing how multiple adhesion molecules can act in synergy to secure arrest. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-018-0519-x) contains supplementary material, which is available to authorized users.